Respuesta :

[tex]\frac{6(n^{2}+2)}{n}[/tex]
[tex]\frac{6(3^{2}+2)}{3}[/tex]
[tex]\frac{6(9+2)}{3}[/tex]
[tex]\frac{6(11)}{3}[/tex]
[tex]\frac{66}{3}[/tex]
[tex]22[/tex]

Answer:

(B) 22

Step-by-step explanation:

The given expression is:

[tex]\frac{6(n^2+2)}{n}[/tex]

Now, substituting the value of n=3 in the above expression, we get

=[tex]\frac{6((3)^2+2)}{3}[/tex]

=[tex]\frac{6(9+2)}{3}[/tex]

=[tex]2(9+2)[/tex]

=[tex]2(11)[/tex]

=[tex]22[/tex]

Thus, the value of the given expression at n=3 will be 22.

Hence, option (B) is correct.

ACCESS MORE